2014
DOI: 10.1186/preaccept-5627314451282443
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 8 is deregulated in urothelial cancer but not a target for efficient treatment

Abstract: Background: Previous studies have shown that class-I histone deacetylase (HDAC) 8 mRNA is upregulated in urothelial cancer tissues and urothelial cancer cell lines compared to benign controls. Using urothelial cancer cell lines we evaluated whether specific targeting of HDAC8 might be a therapeutic option in bladder cancer treatment. Methods: We conducted siRNA-mediated knockdown and specific pharmacological inhibition of HDAC8 with the three different inhibitors compound 2, compound 5, and compound 6 in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
(44 reference statements)
2
11
0
Order By: Relevance
“…The expression of HDAC8 has been determined in several cancer tissues. Upregulation of HDAC8 was detected in colon, urothelial, ovarian and endometrial cancers (13,20,22,23), and high HDAC8 expression was associated with markers of poor prognosis and poor overall survival in neuroblastoma (16). Likewise, our results also showed that HDAC8 were markedly upregulated in both OSCC tissues and OSCC cell lines.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The expression of HDAC8 has been determined in several cancer tissues. Upregulation of HDAC8 was detected in colon, urothelial, ovarian and endometrial cancers (13,20,22,23), and high HDAC8 expression was associated with markers of poor prognosis and poor overall survival in neuroblastoma (16). Likewise, our results also showed that HDAC8 were markedly upregulated in both OSCC tissues and OSCC cell lines.…”
Section: Discussionsupporting
confidence: 70%
“…The most frequently studied and best-characterized human HDACs are HDAC1 and HDAC2. Also, HDAC8 is most recently identified class I HDAC and the role of HDAC8 in normal and cancer cells remains unclear (20,21). The expression of HDAC8 has been determined in several cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following experiments, all cells were treated with 3 nmol/L romidepsin, 0.5 mmol/L givinostat, and 2.5 mmol/L SAHA (approximate IC 50 s in UCCs). Our group has characterized the impact of SAHA on UCCs previously (6,20,21). All HDAC inhibitors, most strongly romidepsin, significantly enhanced the level of acetylated histones H3 and H4 in UCCs (Fig.…”
Section: Hdac Inhibitors Selectively Targeting Hdac1 and Hdac2 Show Smentioning
confidence: 99%
“…In contrast, neither selective inhibition of HDAC8 nor HDAC6 was efficacious (20,21). We therefore sought to evaluate the efficacy of specific HDAC1 and HDAC2 inhibition in urothelial carcinoma cell lines (UCC) by either siRNA-mediated knockdown or specific pharmacologic inhibition with the class I HDAC inhibitors romidepsin (FK228; ref.…”
Section: Introductionmentioning
confidence: 99%